Addressing Administration Challenges Associated With Blinatumomab Infusions: A Multidisciplinary Approach. Issue 4 (July 2018) - Szoch, Stephanie; Boord, Christina; Duffy, Alison; Patzke, Ciera
Abstract : Blinatumomab has shown great potential for patients with chemotherapy-resistant B-cell acute lymphocytic leukemia. Blinatumomab's toxicity profile includes central nervous system toxicities, as well as cytokine release syndrome. Although neurological toxicities associated with blinatumomab are almost always reversible, early detection and intervention of these toxicities is vital to ensure that patients continue their full course of treatment. Guidelines for the preparation and administration of blinatumomab in both inpatient and outpatient settings, as well as a standardized neurological nursing assessment, were developed to ensure safe and effective administration of blinatumomab.